2014
DOI: 10.3892/mmr.2014.2962
|View full text |Cite
|
Sign up to set email alerts
|

Effects of modified Shu-Gan-Liang-Xue decoction combined with anastrozole on osteoblastic proliferation and differentiation of MC3T3-E1 cells

Abstract: Aromatase inhibitors (AIs) are widely used in the treatment of hormone-dependent breast cancer and as a result, aromatase inhibitor-associated bone loss (AIBL) has become a major concern amongst patients receiving AI treatment. Modified Shu-Gan-Liang-Xue decoction (mSGLXD), a clinical prescription, has been used for ameliorating AIBL in patients with breast cancer for decades and has achieved good clinical efficacy. However, the mechanism underlying how mSGLXD influences bone homeostasis and alleviates AIBL ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Appropriate safety of SGLXD has been shown in herb-drug safety/interaction studies [39,59,73,[76][77][78][79][80][81][82][83][84][85][86][87][88][89]. This preliminary research has been limited to China, with Chinese breast cancer survivors and in a Chinese hospital setting.…”
Section: Am J Biomed Sci and Resmentioning
confidence: 99%
“…Appropriate safety of SGLXD has been shown in herb-drug safety/interaction studies [39,59,73,[76][77][78][79][80][81][82][83][84][85][86][87][88][89]. This preliminary research has been limited to China, with Chinese breast cancer survivors and in a Chinese hospital setting.…”
Section: Am J Biomed Sci and Resmentioning
confidence: 99%
“…Experimental studies have confirmed that Shugan Liangxue Decoction reduced tumor volumes in nude mice with or without ovariectomies. The decoction was also shown to dose-dependently downregulate proliferation of estrogen receptor (ER)-positive breast cancer cells (Fu and Li, 2011 ; Zhou et al, 2014 ) and with no significant estrogenic activity (Zhang and Li, 2009 ; Zhou et al, 2015 ). Its antitumor activity may be related to its inhibiting key estrogen synthetase, such as aromatase and steroid sulfatase (STS) (Zhang and Li, 2010 ; Zhou et al, 2014 ), and may also be related to its selective inhibition of estrogen receptor alpha (ERα) (Zhou et al, 2018 ).…”
Section: Formulaementioning
confidence: 99%
“…In vivo studies in mice have shown a synergistic effect when Shugan Liangxue Decoction is used with tamoxifen, as it enhances anti-tumor effect of tamoxifen (Wu and Li, 2008 ) and alleviates tamoxifen's side effects on endometrial thickening (Li et al, 2003 ). In addition, Shugan Liangxue Decoction combined with anastrozole promotes osteoblast proliferation, enhances osteogenesis (Zhou et al, 2015 ), and improves bone metabolism (Liu et al, 2009 ), suggesting that Shugan Liangxue Decoction may improve bone loss caused by endocrine drugs.…”
Section: Formulaementioning
confidence: 99%
“…Aromatase inhibitors (AIs) are commonly used drugs for the treatment of hormone-sensitive breast cancer in postmenopausal females ( 1 ). AIs limit the extra-ovarian production of estrogens, which occurs in fat, the liver and muscles via the aromatization of androgens.…”
Section: Introductionmentioning
confidence: 99%